Non-Titanised Compared to Titanised Polypropylene Meshes Induce a Pro-Inflammatory and Anti-Angiogenic Response in Fibroblast Co-Cultures - Oleksii Protsepko; Philipp Voisard; Nina Ditsch; Melitta Beatrice Köpke; Christina Kuhn; Birgit Urban; Nicole Pochert; Christian Dannecker; Udo Jeschke; Friedrich Pauli; Fabian Garrido; Carl Mathis Wild (Cell Biochemistry and Biophysics, 2026)
Pelvic organs prolapse (POP) can be treated surgically with native tissue or by placing mesh implants in the pelvic floor and vaginal wall. Mesh implants are manufactured from different materials. We previously demonstrated that titanised polypropylene meshes induced different macrophage polarization compared to pure polypropylene meshes. However, these differences were only observed in cell cultures where the meshes were encapsulated by human dermal fibroblasts (NHDF). In this study, we co-cultivated titanised and non-titanised polypropylene meshes with NHDF alone to analyze the immune response of NHDF against different mesh materials. Concentration of proteins in cell culture supernatants were analyzed using multiplex ELISA. We identified a significant increase of VEGF and VEGF-C ( p = 0.001) for both meshes, and the polypropylene meshes induced significant ( p < 0.001) upregulation of sFlt-1, a vascularization inhibitor. Titanised meshes significantly downregulated ( p = 0.034) the pro-inflammatory cytokine IL-16, whereas polypropylene meshes showed no effect on IL-16. Polypropylene meshes significantly reduced ( p = 0.011) the anti-inflammatory cytokine IL-4, while titanised meshes had no effect on IL-4. Polypropylene meshes induce an anti-angiogenic (sFlt-1 upregulation) and pro-inflammatory response. Titanised coating of polypropylene implants reduced proinflammatory cytokines and promoted angiogenesis. These findings have important clinical implications for the postoperative period where fibroblasts play a key role.

sPlotOpen – An environmentally balanced, open‐access, global dataset of vegetation plots - Francesco Maria Sabatini; Jonathan Lenoir; Tarek Hattab; Elise Aimee Arnst; Milan Chytrý; Jürgen Dengler; Patrice De Ruffray; Stephan M. Hennekens; Ute Jandt; Florian Jansen; Borja Jiménez‐Alfaro; Jens Kattge; et al. (Global Ecology and Biogeography, 2021)
Motivation Assessing biodiversity status and trends in plant communities is critical for understanding, quantifying and predicting the effects of global change on ecosystems. Vegetation plots record the occurrence or abundance of all plant species co‐occurring within delimited local areas. This allows species absences to be inferred, information seldom provided by existing global plant datasets. Although many vegetation plots have been recorded, most are not available to the global research community. A recent initiative, called ‘sPlot’, compiled the first global vegetation plot database, and continues to grow and curate it. The sPlot database, however, is extremely unbalanced spatially and environmentally, and is not open‐access. Here, we address both these issues by (a) resampling the vegetation plots using several environmental variables as sampling strata and (b) securing permission from data holders of 105 local‐to‐regional datasets to openly release data. We thus present sPlotOpen, the largest open‐access dataset of vegetation plots ever released. sPlotOpen can be used to explore global diversity at the plant community level, as ground truth data in remote sensing applications, or as a baseline for biodiversity monitoring. Main types of variable contained Vegetation plots ( n = 95,104) recording cover or abundance of naturally co‐occurring vascular plant species within delimited areas. sPlotOpen contains three partially overlapping resampled datasets ( c . 50,000 plots each), to be used as replicates in global analyses. Besides geographical location, date, plot size, biome, elevation, slope, aspect, vegetation type, naturalness, coverage of various vegetation layers, and source dataset, plot‐level data also include community‐weighted means and variances of 18 plant functional traits from the TRY Plant Trait Database. Spatial location and grain Global, 0.01–40,000 m². Time period and grain 1888–2015, recording dates. Major taxa and level of measurement 42,677 vascular plant taxa, plot‐level records. Software format Three main matrices (.csv), relationally linked.